Observation of Candida spp. in the urine of Female Teens : Observation of Candida spp. in the urine of Female Teens - Nurdin, Erpi; Mukhtasyam Zuchrullah; Nofita Sari Djurumudi (Bionature, 2024)
Candida albicans is an opportunistic pathogenic fungus that most often causes urinary tract infections. The presence of C. albicans and NCA species in urine is known as candiduria, which can cause urinary tract infections. The presence of C. albicans in urine is caused because the female urethra is shorter than that of men. Research purposes to determine the frequency distribution and presentation of the presence of Candida spp. in the urine of female adolescents at the Hidayatullah Islamic Boarding School in Ternate City. Method this study uses a descriptive research type. This study describes the presence or absence of Candida spp. in the urine of female adolescents at the Hidayatullah Islamic Boarding School in Ternate City. Research results show obtained 40 urine samples of female adolescents examined, it was found that 14 samples (35%) were positive for C. albicans and 26 samples (65%) were negative for C. albicans. Results of this study concluded that 35% of the urine of female adolescents at the Hidayatullah Islamic Boarding School in Ternate City was infected with C. albicans. Keywords: Candida albicans, candiduria, urinary tract infection